2021
DOI: 10.1007/s40279-021-01590-y
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Signature of Cardiorespiratory Fitness: A Systematic Review

Abstract: Background Cardiorespiratory fitness (CRF) is a potent health marker, the improvement of which is associated with a reduced incidence of non-communicable diseases and all-cause mortality. Identifying metabolic signatures associated with CRF could reveal how CRF fosters human health and lead to the development of novel health-monitoring strategies. Objective This article systematically reviewed reported associations between CRF and metabolites measured in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Aerobic exercise has been shown to modulate circulating ceramide levels [ 64 ]. In particular, cardiorespiratory fitness (CRF), a significant biomarker of health status, the improvement of which is related to a reduced incidence of non-communicable diseases and mortality, resulted as inversely associated to ceramide levels, after analysis in a systematic review reporting the association between CRF and metabolites measured in human tissues and body fluids, and including 22 studies [ 65 ]. In this context, additional therapies directed towards the inhibition of ceramide pathways (e.g., myriocin-inhibitor of serine palmitoyl-CoA transferase, an enzyme involved in up-regulation in de novo synthesis of ceramide), ceramide inhibitors (e.g., Fumonisin B1, fungin FTY720, etc.…”
Section: Ceramides and Cardiometabolic Riskmentioning
confidence: 99%
“…Aerobic exercise has been shown to modulate circulating ceramide levels [ 64 ]. In particular, cardiorespiratory fitness (CRF), a significant biomarker of health status, the improvement of which is related to a reduced incidence of non-communicable diseases and mortality, resulted as inversely associated to ceramide levels, after analysis in a systematic review reporting the association between CRF and metabolites measured in human tissues and body fluids, and including 22 studies [ 65 ]. In this context, additional therapies directed towards the inhibition of ceramide pathways (e.g., myriocin-inhibitor of serine palmitoyl-CoA transferase, an enzyme involved in up-regulation in de novo synthesis of ceramide), ceramide inhibitors (e.g., Fumonisin B1, fungin FTY720, etc.…”
Section: Ceramides and Cardiometabolic Riskmentioning
confidence: 99%
“…We performed an elaborate analysis of 102 circulating biomarkers and metabolic parameters, previously studied in disease conditions such as diabetes type 2, obesity, and cardiovascular disease [ 24 , 25 , 26 , 27 ], but hardly in healthy individuals with different lifestyles. Analysis of a selection of these biomarkers and metabolic parameters across two platforms showed similar results, underpinning their reliability, and indicating the robustness of these platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that all other biomarkers and metabolic parameters were similar between the two groups, while previous studies in high and low aerobically fit individuals found significant differences in e.g., lipid and protein metabolites [ 30 , 31 , 32 , 33 , 34 , 35 ], is likely related to our standardised experimental set-up, as compared to other studies. We studied healthy, young-adult females of similar age and BMI in a highly controlled setting, while previous studies were performed with metabolically impaired individuals [ 26 ], and individuals with substantially different BMIs [ 30 , 31 , 32 , 35 ], or wider age ranges [ 30 , 35 ] in experimental conditions that were less standardised [ 30 , 31 , 32 , 33 , 35 ], and these factors especially impact circulating metabolite levels [ 26 , 30 , 31 ]. Given that the levels of the analysed biomarkers and metabolic parameters were similar among the healthy females in our study, and multiple of these biomarkers and metabolic parameters showed dysregulation during disease, our findings imply that this biomarker and metabolic parameters set could be used to monitor progress from a healthy to an unhealthier state and may be used in health improvement interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by the fact that circulating sphingolipids have been reported to be negatively associated with cardiorespiratory fitness (CRF). 36 Two preliminary studies investigated the effect of exercise on the circulating sphingolipidome. A single bout of moderate-intensity continuous training (MICT) increased circulating sphingolipids in endurance athletes, sedentary obese individuals, and patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%